If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 9 = 4x + 21 Reorder the terms: 9 + 6x = 4x + 21 Reorder the terms: 9 + 6x = 21 + 4x Solving 9 + 6x = 21 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 9 + 6x + -4x = 21 + 4x + -4x Combine like terms: 6x + -4x = 2x 9 + 2x = 21 + 4x + -4x Combine like terms: 4x + -4x = 0 9 + 2x = 21 + 0 9 + 2x = 21 Add '-9' to each side of the equation. 9 + -9 + 2x = 21 + -9 Combine like terms: 9 + -9 = 0 0 + 2x = 21 + -9 2x = 21 + -9 Combine like terms: 21 + -9 = 12 2x = 12 Divide each side by '2'. x = 6 Simplifying x = 6
| 6A+2A=32 | | 6b-29=36 | | 4x^2-13x+5=-5x+2 | | x^2+5x+17=-5x+1 | | 3d-9-8b=11 | | x^2+7x-1=7 | | n^4-13n^2+36=0 | | 5g*4d= | | 11-8x=0 | | x^2+10x-27=8x-3 | | 5x-33=2x+57 | | =0.4(3d-5) | | -2y+3(-2)+5y+35=6y+2(-2)-3y+8 | | 2x+9y=4 | | 2(-2)-3+5y+6=8y-4(-2)+24 | | 3x+7y=6 | | 9(x-2)-4=14 | | -9x+3+5x=2x-3x+3+7-2 | | -x-2y+z=-6 | | 3x/7-5=4 | | 9(x-1)+3x=-9x+5 | | 2x+4y-2z=6 | | 0.42x-5=4 | | x+3y-z=12 | | 5x-y+5z=30 | | 5x-2x+6-4+14=5x-3x+8 | | 3(g-7)-2=4 | | 16=-4-4x | | -x+2y-3z=-9 | | -3t+5=26 | | 4x-2x+3-8=7x-5+4x | | 3t+5=26 |